2016
DOI: 10.1007/s00246-016-1529-x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Inhibition in Shunted Infants on Aspirin at Short and Midterm Follow-Up

Abstract: There are few data to guide aspirin therapy to prevent shunt thrombosis in infants. We aimed to determine if aspirin administered at conventional dosing in shunted infants resulted in ≥50% arachidonic acid (AA) inhibition in short and midterm follow-up using thromboelastography with platelet mapping (TEG-PM) and to describe bleeding and thrombotic events during follow-up. We performed a prospective observational study of infants on aspirin following Norwood procedure, aortopulmonary shunt alone, or cavopulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…This review identified only two studies that reported a statistically significant association between thrombosis outcomes and laboratory values of responsiveness (urinary TxB2 and aspirin response unit), 16,18 and one study that reported a statistically significant association between bleeding and percentage of ADP inhibition (TEG-PM). 12 Notably, these are three observational cohort studies, but a meta-analysis and a systematic review in adults have previously established significant association between cardiovascular complications and resistance as defined by laboratory values. 2,3 Contrastingly, no studies included in this review illustrated or measured a change in clinical resistance after dose adjustments based on laboratory values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review identified only two studies that reported a statistically significant association between thrombosis outcomes and laboratory values of responsiveness (urinary TxB2 and aspirin response unit), 16,18 and one study that reported a statistically significant association between bleeding and percentage of ADP inhibition (TEG-PM). 12 Notably, these are three observational cohort studies, but a meta-analysis and a systematic review in adults have previously established significant association between cardiovascular complications and resistance as defined by laboratory values. 2,3 Contrastingly, no studies included in this review illustrated or measured a change in clinical resistance after dose adjustments based on laboratory values.…”
Section: Discussionmentioning
confidence: 99%
“…Drug compliance was mentioned in 7/20 studies (35%) but not stated as the main purpose of utilizing the monitoring tools. 9,[11][12][13][14][15][16] Antiplatelet Biochemical Resistance and Response…”
Section: Monitoring Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal bleeding is attributed to both decreased prostaglandin synthesis in the gastric mucosa resulting in gastritis and an antiplatelet effect from irreversible COX1 inhibition. Pediatric data describing overall bleeding risks with ASA are limited, but the reported incidence ranges from 2% to 33%, with the highest risks associated with central venous catheter or chest tube sites after cardiac surgery . Pediatric estimates of ASA‐associated gastrointestinal bleeding are even more elusive, because most large studies address bleeding in side‐effect reporting rather than as a primary outcome .…”
Section: Aspirin Side Effectsmentioning
confidence: 99%
“…Pediatric data describing overall bleeding risks with ASA are limited, but the reported incidence ranges from 2% to 33%, with the highest risks associated with central venous catheter or chest tube sites after cardiac surgery. 78,79 Pediatric estimates of ASA-associated gastrointestinal bleeding are even more elusive, because most large studies address bleeding in side-effect reporting rather than as a primary outcome. 80 shown in adults with coronary artery disease (CAD).…”
Section: Aspirin Side Effectsmentioning
confidence: 99%